In Search of an Ideal Closure Method: A Randomized, Controlled Trial of Octyl-2-Cyanoacrylate and Adhesive Mesh versus Subcuticular Suture in Reduction Mammaplasty. Issue 4 (October 2018) - Lee, James C.; Ishtihar, Sherene; Means, Jessica J.; Wu, June; Rohde, Christine H.
Abstract : Background: An ideal wound closure system is one that is effective, consistent, and efficient. Recent studies have demonstrated the efficacy of octyl-2-cyanoacrylate and mesh (Dermabond Prineo) in the closure of surgical wounds. This study compared the use of Prineo to use of subcuticular suture closure in reduction mammaplasty. Methods: A prospective, randomized, controlled, single-blind study of patients undergoing bilateral reduction mammaplasty was performed. Each breast per patient was randomized to layered closure with Prineo or subcuticular sutures. Incisions were assessed at 2 weeks, 6 weeks, 6 months, and 1 year. Subjects completed the Patient and Observer Scar Assessment Scale for each breast, and two blinded plastic surgeons evaluated scar quality using the Vancouver Scar Scale at each time point. Results: Twenty-one patients participated in the study. On average, Prineo closure took 58.38 seconds (2.50 seconds/cm) and subcuticular closure took 444.76 seconds (18.94 seconds/cm). Prineo closure was approximately 6.8 times faster ( p < 0.001) than subcuticular closure, saving an average of 6.4 minutes per incision. Vancouver Scar Scale scores were significantly better in patients with Prineo closure at 2 weeks ( p = 0.026), although there was no difference in Patient and Observer Scar Assessment Scale and Vancouver Scar Scale scores at all other time points. Conclusions: In reduction mammaplasty, Prineo closure results in similar scar quality and lower operative cost without increased complications when compared to subcuticular closure. Prineo is faster than subcuticular closure and represents an effective, consistent, and efficient alternative to subcuticular suture techniques. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.